Confirmation of enrofloxacin, ofloxacin, sarafloxacin and danofloxacin residues in poultry meat and pork via LLE-SPE-GC–MS/MS coupled with derivatization treatment - Junjie Xu; Yiwei Hong; Yun Liu; Shuyu Liu; Pengfei Gao; Yawen Guo; Yang Cao; Hao Ding; Maoda Pang; Tao Zhang; Genxi Zhang; Xiaodong Guo; et al. (Food Chemistry: X)
A gas chromatography-tandem mass technique for simultaneous determination of four fluoroquinolone residues in poultry meat and pork was perfect. Trimethylsilyl diazomethane was applied as the derivatizing agent coupled with liquid–liquid and solid–phase extraction. Full scan mass spectrometry and automated selected reaction monitoring were applied for qualitative and quantitative analysis. The limits of detection of enrofloxacin, ofloxacin, sarafloxacin and danofloxacin were 1.0, 0.2, 1.0 and 1.0 μg/kg, respectively, and limits of quantitation were 2.0, 0.4, 2.0 and 2.0 μg/kg, respectively. The range of recoveries were 77.97–92.23 %. The relative standard deviations were less than 7.45 %. All matrices had weak matrix effects. This method conforms to the requirements of Food and Agriculture Organization of United Nations & World Health Organization (2014) for veterinary drug residue testing, expanding the monitoring range and improving the detection efficiency. Only enrofloxacin residues (2.52–18.32 μg/kg) below maximum residue limits were detected in real samples.